Psychiatrie in meervoud. De wetenschappelijke oriëntaties van de Nederlandse psychiatrie in het interbellum (1918-1940) - Vijselaar, Joost; Abma, Ruud (Studium, 2010)
Psychiatry in multiplicity According to a widespread interpretation, the history of psychiatry is characterized by a strong opposition between biological and psychological paradigms, which would dominate consecutive periods in history. The image of a swinging pendulum is a popular metaphor to describe this idea. The culture of Dutch psychiatry in the interwar years (1918-1940) seems to gainsay this image. Psychological, biological and socials models of explanation and therapy were used alongside each other without apparent debate and conflict. Influential professors of psychiatry like H.C. Rümke (Utrecht University) even pleaded for a conscious integration of these approaches. Some historians have interpreted this stance as a sign of scientific ‘vagueness’ and ‘anarchy’. Analyzing the work of three major representatives of Dutch psychiatry in the Interbellum (Leendert Bouman, Han Rümke and Lammert van der Horst), the authors (former students of the master Historical and Comparative Studies of the Sciences and the Humanities) shed light on the psychiatric climate of this era, dealing with themes like the openness of psychiatry to other sciences, the interactions of psychiatry and literature, and the relationship between theory and clinical practice. As a result a further qualification of the image of the pendulum is argued for.